Hospital Cost vs INA-CBGs Claim for Obstetrics Procedure In Soe Rural General Hospital, East Nusa Tenggara: Tarif Rumah Sakit vs Klaim INA-CBGs untuk Prosedur Obstetrik di Rumah Sakit Umum Daerah SoE, Nusa Tenggara Timur - Yudianto B. Saroyo; Raymond Surya; Ascobat Gani (Indonesian Socety of Obstetrics and Gynecology, 2023)
Objective: To depict the discrepancy and analyze the difference between hospital cost and INA-CBGs claim in obstetrics’ cases in SoE Rural General Hospital, Timor Tengah Selatan regent, East Nusa Tenggara. Methods: This is an observational descriptive study using medical record documents of spontaneous vaginal, assisted vaginal, and cesarean delivery cases from the period of October to December 2022. We included all completed billing documents on that period. Cases paid by fee-for-service and local government were excluded. Data analysis was conducted using IBM SPSS Statistic 23.0 Results: From the total of 323 delivery cases recorded in SoE Rural General Hospital, only 245 cases were included. Most subjects were patients aged around 30 years old, referred from primary healthcare facility in the district, were in term pregnancy, and in 3rd class inpatient rooms. The median of length of stay (LOS) in vaginal delivery (spontaneous and assisted) and cesarean delivery were 2 days and 3 days, respectively. Mean difference between hospital cost to INA-CBGs claim was 67% to 158% for either vaginal or cesarean delivery based on class inpatient room. We found that hospital cost was always higher than claim cost based on INA-CBGs claim. Conclusion: There is a significant discrepancy between hospital cost and INA-CBGs claim (from 67% to 158%) for obstetric services in SoE Rural General Hospital. Keywords: hospital cost, INA-CBGs claim, obstetric. Abstrak Tujuan: Untuk memberikan gambaran perbedaan dan menganalisis perbedaan antara tarif RS dengan klaim INA-CBGs pada kasus obstetrik di RSUD SoE, Timor Tengah Selatan, Nusa Tenggara Timur. Metode: Studi deskriptif observasional menggunakan dokumen rekam medis dari kasus persalinan pervaginam spontan, persalinan pervaginam dengan alat, dan seksio sesarea dari Oktober hinga Desember 2022. Kami memasukkan seluruh dokumen billing yang lengkap. Dokumen biling yang dibayarkan mandiri dan oleh pemerintah lokal dieskslusi. Analisis data dengan menggunakan IBM SPSS Statistik 23.0. Hasil: Dari 323 persalinan yang terekam di RSUD SoE, hanya 245 kasus diinklusikan. Kebanyakan subjek berusia 30 tahun, dirujuk dari puskesmas, kehamilan cukup bulan, dan ruang perawatan kelas 3. Angka median dari lama rawat pervaginam (baik spontan maupun dengan alat) adalah 2 hari dan seksio sesarea 3 hari. Rerata perbedaan tarif RS dengan klaim INA-CBGs ialah 67% hingga 158% baik persalinan pervaginam maupun seksio sesarea berdasarkan ruang kelas perawatan. Kami menemukan angka tarif RS selalu lebih tinggi cukup jauh dari klaim INA-CBGs. Kesimpulan: Terdapat perbedaan antara tarif RS dan klaim INA-CBGs (antara 67 hingga 158%) untuk prosedur obstetrik di RSUD SoE. Kata kunci: tarif RS, klaim INA-CBGs, obstetrik.